An Analysis of Students’ Politeness Strategies in Whatsapp Group Interaction - Mariska Febrianti; Yuneva Yuneva (Edu-Ling: Journal of English Education and Linguistics, 2023)
TOEFL and Abstract is the title of whatsapp group made by UPT Bahasa Inggris Unived to communicate between admin and students who wants to graduate. This is also as the alternative way during the pandemic of Covid-19. This study aimed to analyze students’ politeness strategies from all faculties are in UNIVED and admin of UPT Bahasa Inggris in whatsapp group. Type of this research is descriptive qualitative research. The data were collected through the the transcript during the conversation between admin and undergraduate students. The results of this research showed that there were 144 conversations used by students in whatsapp grup. The researchers found 34 were used bald on record, 48 used positive politeness, 53 used negative politeness, and 9 used off-record. Negative politeness was dominant types of politeness among the other types of politeness, that oriented by the speaker as undergraduate students with admin of UPT Bahasa Inggris UNIVED Bengkulu. Question Hedge with 100% were as a form of negative politeness used by undergaduate students. From the results aboves, it shows that the dominant type of Politeness Strategies used by teacher and students in Whatsapp Group are Positive Politeness and Negative Politeness. Keywords: Politeness Strategy, Students Interaction.